Respiratory Complex II and SCOT-Oxct1 Compete for succinyl-CoA in Ketolytic Dependent Tumours - Israël, Maurice; Berg, Eric; Tenenbaum, Guy (British Journal of Healthcare and Medical Research, 2024)
The present work recalls main features of tumour cell metabolism, explaining their ketolytic dependency and vulnerability; we explored the interface between the respiration chain complexes and the nutritional supply of succinyl-CoA to the ketolytic enzyme SCOT- Oxct1. We indicated several target points in ketolysis and fatty acid synthesis pathways that would affect tumour cells, rendered vulnerable by their ketolytic dependency.